2016
DOI: 10.11648/j.aff.20160502.11
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Storage and Climate Change Mitigation Potential of the Forests of the Simien Mountains National Park, Ethiopia

Abstract: Abstract:The study assessed land cover change, carbon stock and sequestration potential of Simien Mountains National Park (SMNP), Ethiopia. Landscape was stratified into four zones based on the vegetation ecology and land uses: Afro-alpine grassland (AAGL), Afro-alpine woodland (AAWL), Afro-montane forest (AMF) and Cultivated and overgrazed land (COL). 40 sample plots were taken randomly (10 from each zone). Nested plot design with size of 50m*50m and subplots of 20m*20m, 10m*10m, 5m*5m, 2m*2m and 1m*1m was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…From the carbon pools (AGBC, BGBC, LHGC, and SOC) in this study, SOC pool was the largest carbon pool (86% of the total ecosystem carbon pools in the restored land and 97% in the unrestored land use types). This has confirmed with the reports of Chinasho et al (2015), in which 55.5% of the total ecosystem carbon pool were SOC in forest ecosystem; Assaye and Asrat (2016), who had reported the largest SOC percentages (74.43%) of the total ecosystem carbon pools. Moreover, ; Ullah and Amin (2012); Mekuria (2013); Hailu (2017) had reported the largest SOC pool in the natural forest ecosystem than biomass and litter carbon pools; whereas, Ordonez et al (2007), had reported the lower SOC pool than the biomass carbon pool.…”
Section: Ecosystem Carbon Stockssupporting
confidence: 89%
“…From the carbon pools (AGBC, BGBC, LHGC, and SOC) in this study, SOC pool was the largest carbon pool (86% of the total ecosystem carbon pools in the restored land and 97% in the unrestored land use types). This has confirmed with the reports of Chinasho et al (2015), in which 55.5% of the total ecosystem carbon pool were SOC in forest ecosystem; Assaye and Asrat (2016), who had reported the largest SOC percentages (74.43%) of the total ecosystem carbon pools. Moreover, ; Ullah and Amin (2012); Mekuria (2013); Hailu (2017) had reported the largest SOC pool in the natural forest ecosystem than biomass and litter carbon pools; whereas, Ordonez et al (2007), had reported the lower SOC pool than the biomass carbon pool.…”
Section: Ecosystem Carbon Stockssupporting
confidence: 89%
“…Most research suggests that soil organic carbon exceeds above-ground carbon (carbon in vegetation). This finding is also aligned with the investigation of (Girmay et al 2008;Chinasho et al 2015;Assaye & Asrat 2016;Bikila et al 2017) also suggested that more than 90% of the total carbon stock was contributed from soil organic carbon in the wooded grassland.…”
Section: Soil Organic Carbonsupporting
confidence: 85%
“…Forests absorb carbon emitted from various sources, including industry, agriculture, residences and energy production, by sequestering and storing it. Assaye and Asrat's [ 43 ] study also focused on the same case study. The authors found that above-ground carbon held 34.4% of the total carbon stocks in Simien Mountains National Park, while below-ground carbon contained 8.3% of the carbon stocks.…”
Section: Literature Reviewmentioning
confidence: 99%